2004
DOI: 10.1073/pnas.0305411101
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional association of RNA polymerase II and the proteasome

Abstract: Recent studies from a number of laboratories have revealed a surprising number of connections between RNA polymerase II transcription and the ubiquitin͞proteasome pathway. We now find yet another intersection of these pathways by showing that the 26S proteasome associates with regions of the GAL1, GAL10, and HSP82 genes, including the 3 ends, in a transcription-dependent fashion. The appearance of the proteasome on these inducible genes correlates with both the accumulation of transcripts and the buildup of RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 27 publications
13
132
0
1
Order By: Relevance
“…UBLCP1 has been shown to dephosphorylate the CTD of RNA polymerase II in vitro (40). In addition, recent studies have physically and functionally linked the 26 S proteasome with RNA polymerase II in vivo (41). Together with the findings reported here, these results raise the possibility that UBLCP1 may be a shuttling factor that links the proteasome complex to transcriptional control.…”
Section: -H Map-silacsupporting
confidence: 78%
“…UBLCP1 has been shown to dephosphorylate the CTD of RNA polymerase II in vitro (40). In addition, recent studies have physically and functionally linked the 26 S proteasome with RNA polymerase II in vivo (41). Together with the findings reported here, these results raise the possibility that UBLCP1 may be a shuttling factor that links the proteasome complex to transcriptional control.…”
Section: -H Map-silacsupporting
confidence: 78%
“…The requirement for transcription for the assembly of the polyubiquitin chains on Top1 is interesting. Previous studies have suggested that proteasome components are associated with RNA polymerase II and are required for efficient transcription elongation (37,38). It is possible that the collision between the Top1 cleavage complex and the elongating RNA polymerase may bring the proteasome components into close proximity of the colliding complexes and facilitate proteasomal degradation of Top1.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Moreover, a number of transcripts encoding proteasome-associated and F-box proteins were identified in Arabidopsis developing and germinating pollen. 42,54 Proteasomes were also demonstrated to perform other nonproteolytic functions including transcriptional regulation, [55][56][57] RNase activity, 58,59 translational regulation, 60,61 and possessing cytoskeleton-binding properties. 52,62 With regard to all abovementioned alternative functions, the presence of proteasome subunits within EPP complexes is natural in relation to complex EPP-associated spatially and temporarily regulated activities.…”
Section: Discussionmentioning
confidence: 99%